A Highly Stretchable Tough Polymer Actuator Driven by Acetone Vapors. Issue 1 (2nd November 2018) - Yuan, Yihui; Yuan, Jun; Tan, Huiyan; Song, Xiaodong; Tu, Yaqing; Zhang, Ting; Han, Huijing; Huang, Wei; Huang, Xinhua; Zhang, Lidong
Abstract: Stimuli‐responsive polymer materials having high stretchability and robust toughness are more promising for applications in wearable electronics, soft robotics, and sensors. Herein, a micropatterned single‐layered polymer soft actuator is reported that can be stretched to 600% of its original length with the strength reaching 40 MPa. The prominent mechanical stretchability comes from the modification of poly(vinylidene fluoride) (PVDF) by using 3‐methacryloxypropyltrimethoxysilane (MS), followed by the treatment with mechanical uniaxial stretching. The uniaxial stretching induces microscopic patterning of the PVDF/MS composite actuator, making it capable of kinematics‐controllable movements in response to acetone vapors. The mechanically strong single‐layered vaporesponsive PVDF/MS actuator overcomes many drawbacks of polymer bilayer actuators that might undergo interfacial failure and inactivation caused by less‐than‐perfect mechanical properties. Driven by acetone vapors, the PVDF/MS actuator demonstrates highly efficient energy conversion and sensing abilities with simulating artificial muscles for inducing the movements of various paper dolls. Abstract : A micropatterned single‐layered polymer soft actuator is reported. The actuator is capable of kinematics‐controllable movements in response to acetone vapors, and overcomes many drawbacks of polymer bilayer actuators that may undergo interfacial failure and inactivation caused by less‐than‐perfect mechanical properties.